Memory in Written Record: Memorial Practices at Work in Middle English Copyings of Flyleaf, Marginal and Added Verse. (11th March 2022) - Wilson, Rowan
Abstract: This article focuses on the memorial practices evidenced in Middle English copyings of flyleaf, marginal and added verse—'flyleaf verses'. These texts, typically added by later readers or book-users, are often characterized as errant incursions into the book's organization, ephemeral traces of aural memory, mere scribbles copied without care and preserved only by chance. However, closer study reveals a variety of memorial processes underlying flyleaf verse copying, ranging from the casual jottings from memory that dominate existing scholarly perspectives, to using book-space for the deliberate practice of memorization, to copying purposefully to collect and preserve verses. This article surveys 523 records from the Digital Index of Middle English Verse (DIMEV) that contain at least one witness of a text added in a flyleaf, margin, or other blank book-space, as well as several digitized and facsimile copies of the manuscripts in which they appear. These records complicate understandings of memory's active use in flyleaf verse copying, offering us insights into the mental processes behind medieval readers' engagement with the marginal spaces in their books.